A Effectiveness differentiation of additional kinesiotaping on ultrasound and plantar fasciitis exercises in increasing functional foot in plantar pain conditions - Ari Wibawa; Ni Luh Nopi Andayani; Gede Parta Kinandana (Bali Anatomy Journal, 2021)
Background: Plantar fasciitis is an inflammation of the tissue that extends from the heel to the toes. Plantar fasciitis can cause disability in patients Aim: This study aimed to prove the differentiation of additional kinesiotaping to ultrasound intervention and plantar fasciitis exercise for plantar pain conditions. Methods: The study applied a pre-test and post-test control group design. The block permutation technique randomly selected two groups. The first group consisted of 15 samples who received kinesiotaping intervention, ultrasound, plantar fasciitis exercise. Group II (15 samples) received ultrasound and plantar fasciitis exercise. Disability was measured by the FFI (Foot Function Index) questionnaire. The study was conducted at physiotherapy clinics in Denpasar and Badung Results: Paired t-test was carried out in each group with a p-value <0.05, indicating a decrease in disability between the two groups. The difference test was carried out with the independent t-test (p > 0.05), implying no difference between group I and group II. Conclusion: There is no difference in the effectiveness of adding kinesiotaping to ultrasound intervention and plantar fasciitis exercises in improving foot function.